Influence of Design and Cutting Conditions On the Accuracy of the Hole Obtained by Drills with Multifaceted Non-Regrind-Able Inserts (MNP) - Umarov, Tolibjon; Turonov, Mukhammadi; Meliboyev, Yahyojon (International Journal of Integrated Engineering, 2023)
Drills with MNPs have a fundamental design difference from spiral drills, expressed in increased rigidity of the body, a change in geometry and the absence of a wide gauging part. In this article, taking into account the kinematic cutting angles and the real design of the tool, recommendations are given for determining the maximum allowable feed. The shape of the machined hole is proved to a large extent by the ratio of the angular velocities of the precession of the drill axis and its own frequency of rotation.